2005
DOI: 10.1111/j.1440-1827.2005.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression patterns of claudin‐1 and claudin‐4 in intraductal papillary–mucinous tumors of the pancreas

Abstract: The expression of claudin-4 was investigated in human pancreas, pancreatic ductal adenocarcinomas, and intraductal papillary-mucinous tumors of the pancreas (IPMT), and compared with that of claudin-1. In human adult pancreatic specimens, both claudin-1 and claudin-4 were immunohistochemically found in main and branching pancreatic ducts, terminal ductules and acinic cells, with the exception of endocrine cells. Of 12 cases of pancreatic ductal adenocarcinoma, 11 (92%) had positive immunostaining for claudin-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
(20 reference statements)
2
24
0
Order By: Relevance
“…Our results are consistent with a previous immunohistochemical analysis showing a positive correlation between CLDN4 protein expression and histological tumor grades in intraductal papillary mucinous neoplasms. 29 The mechanism underlying the overexpression of CLDN4 in intraductal papillary mucinous neoplasms remains unclear, but a previous study has shown an association between CLDN4 overexpression and gene hypomethylation in pancreatic cancer cells. 26 In the present study, we analyzed the relationship between CLDN4 expression and papillary subtypes of intraductal papillary mucinous neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with a previous immunohistochemical analysis showing a positive correlation between CLDN4 protein expression and histological tumor grades in intraductal papillary mucinous neoplasms. 29 The mechanism underlying the overexpression of CLDN4 in intraductal papillary mucinous neoplasms remains unclear, but a previous study has shown an association between CLDN4 overexpression and gene hypomethylation in pancreatic cancer cells. 26 In the present study, we analyzed the relationship between CLDN4 expression and papillary subtypes of intraductal papillary mucinous neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…It creates a charge-selective pore in the paracellular pathway across the epithelia and selectively restricts passage of sodium in the paracellular space. 27 Significant increase of claudin-4 has been detected in pancreatic, 22,28 prostate, 20 cervical 26 and ovarian cancers. 29 For the first time, our study detected high expression of claudin-4 in biliary tract cancers in contrast to hepatocellular carcinomas at both RNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is also shown that Claudin 1 expression induces cell growth by increasing expression of TNF-α in pancreatic cancer cell (Kondo et al, 2008). Pancreatic ductal adenocarcinomas as well as intraductal papillary mucinous tumours of the pancreas express claudins 1 and 4, and claudin 18 is present mainly in pancreatic carcinoma (Tsukahara et al, 2005;Karanjawala et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Borka et al (2007) showed expression of Claudin 1, 4 and 7 in pancreatic adenocarcinoma (Borka et al, 2007). Tsukahara et al (2005) investigated the expression of claudin-4 in human pancreas, pancreatic ductal adenocarcinomas, and intraductal papillarymucinous tumors of the pancreas (IPMT), and compared with that of claudin-1. Of 12 cases of pancreatic ductal adenocarcinoma, 11 (92%) had positive immunostaining for claudin-4, and seven (58%) for claudin-1 (Tsukahara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation